Application of rice shell activated carbon for reduction of chemical oxygen demand limit and adsorption of iron from abattoir wastewater - Robinson Davi Udo; Samuel Ayegu Tsebam; Kolade Olawale Samson; Precious Nya Umo; Adeniyi Solomon Lawal; Juliet Gordon; Oluwaseun Fetuata; Ibrahim Ademola Fetuga; Olabode Thomas Olakoyejo; Antonio Marcos de Oliveira Siqueira (The Journal of Engineering and Exact Sciences)
In this investigation, rice shell (RS)-activated carbon (AC) - (RS-AC) is used as a bio-sorbent to reduce chemical oxygen demand (COD) and adsorb iron from effluent from an abattoir. With H3PO4, the rice husk was altered and chemically activated. Scan electron microscopy (SEM) as well as Fourier-Transform-Infrared (F-T-IR) were utilized to examine the activated RS and examine its content, appearance, and structure. Moreover, proximate analytical study was used to ascertain the activated rice husk's wetness, volatile matter, ash, bulk density, and fixed carbon contents. Contact period, temperature, and dosage are the adsorption parameters that are assessed. The contact period of 10, 20, 30, 40, 50, and 60 min, the dosage of 0.1, 0.2, 0.3, 0.4, 0.5, and 0.6g, and the temperature of 20, 40, 60, 80, and 100oC were evaluated for the Fe bio-adsorption as well as COD limits reduction in wastewater obtained from abattoir at constant agitation of 200rmp and potential hydrogen level of 5 for all the runs. RS-AC can be used to maintain the amount of iron and COD in aqueous solutions and water treatment, according to the results. According to this investigation, ARH has a high fixed carbon content, which makes it an efficient bio-adsorbent, and the resulting RS-AC has a good bulk density for flow consistency. The FI-M best matches the linear equation for iron removal, whereas the LI-M given that the coefficient of correlation that well matches the equation to have COD limit at acceptable level. In comparison to other models, second ordered Kinetics model-SOKM satisfactorily describes current data to keep Fe as well as COD levels within standard ranges; as a result, chemical adsorption controls the bio-adsorption process.